Sooner or later - Macomber, Debbie (HarperPaperbacks, 1996)
No one in the tiny town of Boothill, Texas, knows the real Shaun Murphy--and that's the way he likes it. But he can't hide from the pretty young postmistress, Letty Madden. Letty's brother is missing, and Murphy can help her find him. But when Letty comes to him for help, he makes her a very indecent proposal.